Assessment of fetal motion to improve the quality of diffusion tensor techniques in fetal MRI. (18th April 2012) - Estrin, G Lockwood; Allsop, J; Malamateniou, C; Hajnal, J; Rutherford, M
Abstract : Diffusion tensor imaging allows objective assessment of brain microstructure, but unpredictable fetal movement presents challenges to the antenatal application of this magnetic resonance imaging (MRI) technique. This study aimed to identify factors which influence fetal head motion, in order to implement measures which could decrease fetal motion and improve image quality. 120 pregnant (7 controls) women had a pre-MRI scan motion-assessment. A visual analogue scale assessed maternal anxiety (scale: 0-10cm). Other monitored factors included: pre-scan maternal food and caffeine intake and exercise, temperature, BMI, music during scan, gestational age (GA), sex and lie of the fetus, twins or singletons, reason for scan and fetal motion at different times during scanning. Fetal head motion was graded on a 3-point scale relating to shifting away from a predefined axis in each slice of T2-weighted dynamic scans; the sum of movements comprised the motion score. Maternal and gestational age range was 18-49years and 20 +3 -38 +5 weeks respectively. Difference between anxiety scores before and after scanning ranged from 0-6.7cm. Fetal head motion scores ranged from 3-153. Fetal head motion increased significantly with decreasing GA (p<0.05). A significant reduction in fetal head motion in control compared to clinical scans was found (p<0.05). No other correlations were significant (taking fetal GA into account), suggesting that fetal head motion cannot be reduced using information from a pre-scan motion-assessment. Maternal anxiety did not affect fetal motion, but a significant decrease in anxiety was found immediately after scanning (p<0.05), indicating that measures could be implemented to decrease maternal anxiety before scanning.